CWNA : - Wireless, Planet 3 (McGraw-Hill, 2005)
Written by the company that created the Certified Wireless Network Administrator program, this offical study guide provides all the information you’ll need to help you pass the exam. Get an introduction to wireless LANs and radio frequency technology. Learn about wireless LAN infrastructure devices, antennas, the 802.11 network architecture, MAC and physical layers, and much more. Be prepared to troubleshoot installations and implement security measures. This is the only official CWNA book on the market!